The distribution of well-being among Europeans - Andrea Brandolini; Alfonso Rosolia (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We analyse the evolution of EU citizens' living standards, considering the EU as a single country. Average living standards have improved considerably as the European integration process has unfolded. EU28 income inequality has steadily declined, mostly as a result of the macroeconomic convergence of new EU-accession countries. EU15 income inequality fell steadily until the mid-1980s, but picked up again during the economic turmoil following the Great Recession, largely reflecting the divergence between periphery and core countries in the euro area. Using a common EU standard reveals more progress in terms of poverty reduction. It also shows that the patterns of income convergence across member states differ across categories of residents, thus calling for a more careful consideration of the personal and national dimensions of EU policies.
Keywords: D31; D63; E01; I32; 330; European Union; Euro Area; European integration; income inequality; welfare analysis